Farmer Institutional Dynamics in Vegetable Agribusiness Development Efforts in Kelurahan Talang Keramat, Banyuasin District - Yulian Junaidi; Yulius Yulius; Elly Rosana; Ogi Falma Manullang (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2021)
Farmers' institutions, whether fostered by the government or those that have emerged from the initiatives of non-governmental organizations (NGOs), have an important position in developing vegetable agribusiness. This research aimed to compering the institutional dynamics of government-assisted farmers and non-government organizations and to formulate a collective learning institutional framework. The survey method was carried out by taking disproportional stratified random sampling, the data were analyzed using scoring, chi-square crosstabs and SWOT analysis. The results of this study indicate that the institutional dynamics of farmers are on average in moderate criteria with differences in dynamic indicators. Government-assisted groups prioritize achieving agribusiness goals, while NGO-assisted groups develop an egalitarian structure. Factors that significantly influence the institutional dynamics of farmers are farmer age, education, status in the organization, and access to credit. The joint learning framework from the technological aspect is aimed at discovering, sharing and using vegetable agribusiness development technology. Meanwhile, from the institutional aspect, it is aimed at strengthening organizations and networks.